Kunst als medicijn / volksgezondheid. - Grosfeld, Govert; Janssen, Nanda; Linders, Dees; Melis, Liesbeth; Stroband, David; Van Kampen, Martine; Wagemans, Fred; de Ven, Rob van; van Gestel, Tom; van den Berg, Mariska (Amsterdam : SKOR (Stichting Kunst en Openbare Ruimte), 2005)
Aarsman, Hans ; van Bergen, André ; Janssens, Ann Veronica ; Katzir, Ram ; Kinoshita, Suchan ; Lester, Gabriël ; van Lieshout, Erik ; Luijters, Rudy J. ; Monahan, Matthew ; Müller, Marc ; de Pavert, Jan van ; Tee, Jennifer ; van Wijk, Famke ; Zwakman, Edwin
boek